From Partnered to Single: Financial Security Over a Lifetime - Broadway, Barbara; Kalb, Guyonne; Maheswaran, Dhanya (My University, 2022)
When a relationship breaks down, women are at a much higher risk of falling into poverty than men—especially if they have children to care for. This report uncovers new research that suggests that while a separation can reduce a man’s disposable household income by 5 per cent, on average a women’s household income decreases by almost 30 per cent. The most vulnerable group to fall into this ‘poverty trap’ were women who were without a job before the break up, and women with children. While those who had secure employment and those with a tertiary education fared much better. It is likely that women who are worse off after a separation are so due to the interplay between childcare costs and the income support system where the loss of support payments and the extra cost of childcare erode the benefit of having a job. Unfortunately, this trap looks worse for older women. While women with young children who had no job before separation have usually only been out of the labour force for a short time, women with older children and no job at separation have typically been disconnected from the labour market for longer, meaning their job prospects are lower.
Keywords: Disadvantage, adversity and resilience; Families and relationships; Income, wealth and finances; Labour market